Karakteristik Permukiman Kumuh di Kota Solok - Lara Odia Apriyanti (JURNAL BUANA, 2022)
This study aims to determine the research in the city of Solok. The approach used in this study is a qualitative descriptive method with the following steps. The results of the study indicate the following: 1. Characteristics of the building: a) the condition of the building in which there are 3 RTs is not in accordance with the technical requirements. b) building density there are 2 RTs which have high building density. c) the distance between buildings is 1.5 – 2 meters. 2. Characteristics of facilities and infrastructure: a) the condition of the roads in the 2 RTs is inadequate. b) the condition of the clean water infrastructure is that there are 2 RTs that are not sufficient. c) MCK conditions in all RT according to technical requirements. d) the condition of the waste there are 19 RTs that are not maintained. e) the drainage condition of 5 RT is not sufficient. 3. Social characteristics: a) population density there are 11 RTs with a high density level. b) income level there are 14 high-income households. then the level of severe slums in 4 RT and 16 RT with a moderate level of slums.